Continuing education interventions about person-centered care targeted for nurses in older people long-term care: a systematic review - Pakkonen, Mari; Stolt, Minna; Charalambous, Andreas; Suhonen, Riitta (My University, 2021)
Background: Person-Centered Care is often seen as an indicator of quality of care. However, it is not known whether and to what extent person-centered care can be enhanced by continuing education interventions in older people’s long-term care settings. This systematic review aimed to analyze and synthesize the existing research literature about person-centered care-based continuing educational interventions for nurses working in long-term care settings for older people. Methods: Five databases were searched 6/2019 and updated 7/2020; PubMed (Medline), CINAHL, PsycINFO, Cochrane and Eric using the keywords person-centered car* OR person-centred car * OR patient-centered car* OR client-centered car* OR tailored car* OR resident-centered car* OR individualized car* AND older* OR elder* OR old person* AND Long-Term Care OR Nursing home OR 24-h treatment OR long-term treatment. Twenty-seven full texts from 2587 initially retrieved citations were included. Results: The continuing educational interventions found were divided into five themes: person-centered interventions focusing on medication; interaction and caring culture; nurses’ job satisfaction; nursing activities; and older people’s quality of life. The perspective of older people and their next of kin about the influence of continuing education interventions were largely absent. The background theories about interventions, the measurements taken, and the clarity around the building blocks of the continuing-care interventions need further empirical verification. The pedagogical methods used were mainly quite behavioristic mostly lectures and seminars. Conclusion: Most of person-centered care continuing education interventions are effective. Still more empirical research-based continuing education interventions are needed that include learner-centered pedagogical methods, with measurable outcomes that consider the opinions of older people and their next of kin. Continuing educational interventions for nurses need to be further developed to strengthen nurse’s competence in person-centered care, job satisfaction and for better quality of care.
Keywords: Person-centered care; Continuing education; Older people; Long-term care; Intervention; Review